Autonomous monitoring framework for cellular networks - Trujillo, José Antonio; De la Bandera Cascales, Isabel; Burgueño Romero, Jesús; Palacios, David; Barco-Moreno, Raquel (My University, 2022)
The arrival of a new generation of mobile networks as 5G (5th Generation), brings with it greater complexity in the management of the network due to new services and scenarios. In this context, SON (Self-Organizing Networks) becomes a key factor, given its ability for automate tasks and reduce human workload. Monitoring the network turns out be a crucial task, as it acts as the basis for the other SON functions. This paper proposes a methodology for automate monitoring of mobile networks based on their KPI (Key Performance Indicator).
Keywords: Redes de banda ancha - Congresos; Transmisión digital - Congresos; Monitoring; Self-Organizing Networks; 5G; KPI; Mobile Communications